Transformation of taxi industry: the establishment of Service Level Agreement for taxi licence holder / Ahmad Zaffley Ahmad Zahudi - Ahmad Zahudi, Ahmad Zaffley (2015)
Service Level Agreement (SLA) for taxi licence holder is an agreement regarding the guarantees of the taxi service. It defines mutual understandings and expectations of a service between regulator and taxi operators. Service guarantees define what transactions need to be executed and how well they should be executed. The establishment of the SLA is intended to protect both the regulator and taxi licence holder. SLA is critically important as it helps regulator to effectively monitor the performance of taxi licence holder at the same time it defines impact of a failure service level objective. In a typical scenario, each service interacts with other services, switching between roles of being a provider (regulator and taxi operator) in some interactions and being a passenger in other interactions. Each of these interactions could potentially be governed by a SLA. To ensure that the taxi licence is given to the right parties, taxi licence holder needs to sign the SLA prior to getting the licence by the regulator. In this regards, it is important that SLA is prepared so that it would be able to balance the risks and benefits of all parties. This balance should be based on good understanding of impact of various service levels on business processes relating to both regulator and taxi licence holder. SLA would be a mechanism to define specific service level procedures hence, further strengthening the existing conditions attached to legislations that govern matters related to taxi industry, which currently are too general. Successful service organizations understand well the importance of carefully monitoring and managing customer satisfaction. In this regards, the most successful way of recovering from any service failure is to make things right, eliminating the cause of dissatisfaction with the initial service.